Efficient earmarking under decentralized fiscal commitments - Silva, Emilson Caputo Delfino (International tax and public finance, 2015)
Earmarked federal grants are ubiquitous and significant. Traditional fiscal federalism is unable to explain these grants’ widespread utilization. Recent arguments focusing on the potential benefits of centralized earmarking in reducing incentives for the creation of soft budgets at subcentral government levels merit formalization. I show that universal earmarking improves the efficiency of a federation in which regional governments are able to commit to provision of all regional public goods. However, efficient earmarking need not be universal: It should only involve private consumption and fiscal budgets for public goods subject to decentralized fiscal commitments.